Abnormal Chloride Homeostasis in the Substancia Nigra Pars Reticulata Contributes to Locomotor Deficiency in a Model of Acute Liver Injury - Yang, Yan-Ling (Public Library of Science, 2013)
BACKGROUND: Altered chloride homeostasis has been thought to be a risk factor for several brain disorders, while less attention has been paid to its role in liver disease. We aimed to analyze the involvement and possible mechanisms of altered chloride homeostasis of GABAergic neurons within the substantia nigra pars reticulata (SNr) in the motor deficit observed in a model of encephalopathy caused by acute liver failure, by using glutamic acid decarboxylase 67 - green fluorescent protein knock-in transgenic mice. METHODS: Alterations in intracellular chloride concentration in GABAergic neurons within the SNr and changes in the expression of two dominant chloride homeostasis-regulating genes, KCC2 and NKCC1, were evaluated in mice with hypolocomotion due to hepatic encephalopathy (HE). The effects of pharmacological blockade and/or activation of KCC2 and NKCC1 functions with their specific inhibitors and/or activators on the motor activity were assessed. RESULTS: In our mouse model of acute liver injury, chloride imaging indicated an increase in local intracellular chloride concentration in SNr GABAergic neurons. In addition, the mRNA and protein levels of KCC2 were reduced, particularly on neuronal cell membranes; in contrast, NKCC1 expression remained unaffected. Furthermore, blockage of KCC2 reduced motor activity in the normal mice and led to a further deteriorated hypolocomotion in HE mice. Blockade of NKCC1 was not able to normalize motor activity in mice with liver failure. CONCLUSION: Our data suggest that altered chloride homeostasis is likely involved in the pathophysiology of hypolocomotion following HE. Drugs aimed at restoring normal chloride homeostasis would be a potential treatment for hepatic failure.